113k views
1 vote
17. Let f(x) = 2x2 + 5x + 6 and g(x) = 3x2 + 4x – 10.

a Find f(x) + g(x)
b. Find f(x) – g(x)

2 Answers

2 votes
f(x)+g(x)= (2x^2+5x+6)+(3x^2+4x-10)= 5x^2 + 9x -4.
f(x)-g(x)= (2x^2+5x-6)-(3x^2+4x-10)= 2x^2+5x-6 (-3x^2 - 4x +10)= -x^2 +x+4
User Simon Hellinger
by
4.3k points
5 votes

Explanation:

f(x)+g(x)=(2x^2 + 5x +6) + (3x^2 +4x - 10)

Combine like terms

5x^2 + 9x -4

f(x)-g(x)=(2x^2 + 5x +6) - (3x^2 +4x - 10)

Distribute the negative

(2x^2 + 5x +6) + (-3x^2 -4x + 10)

Combine like terms

-x^2 +x +16

User Raeanne
by
4.9k points